Bone marrow mesenchymal stem cells paracrine TGF-β1 to mediate the biological activity of osteoblasts in bone repair. (April 2023) - Zhang, Xiuzhi; Wang, Guangkuo; Wang, Weidan; Ran, Chunxiao; Piao, Fengyuan; Ma, Zhijie; Zhang, Zhaodong; Zheng, Guoshuang; Cao, Fang; Xie, Hui; Cui, Daping; Samuel Okoye, Chukwuemeka; et al.
Graphical abstract: Highlights: The paracrine function of BMSCs play key roles in the process of bone repair. TGF-β1 produced by BMSCs enhanced the osteogenic activity of osteoblasts. TGF-β1 mediated the BMSC-induced osteogenesis and migration of osteoblasts. There was intercellular communication between BMSCs and osteoblasts in bone repair. Abstract: Background: Bone marrow mesenchymal stem cells (BMSCs) are an important source of seed cells for regenerative medicine and tissue engineering therapy. BMSCs have multiple differentiation potentials and can release paracrine factors to facilitate tissue repair. Although the role of the osteogenic differentiation of BMSCs has been fully confirmed, the function and mechanism of BMSC paracrine factors in bone repair are still largely unclear. This study aimed to determine the roles of transforming growth factor beta-1 (TGF-β1) produced by BMSCs in bone tissue repair. Methods: To confirm our hypothesis, we used a Transwell system to coculture hBMSCs and human osteoblast-like cells without contact, which could not only avoid the interference of the osteogenic differentiation of hBMSCs but also establish the cell–cell relationship between hBMSCs and human osteoblast-like cells and provide stable paracrine substances. In the transwell coculture system, alkaline phosphatase activity, mineralized nodule formation, cell migration and chemotaxis analysis assays were conducted. Results: Osteogenesis, migration and chemotaxis of osteoblast-like cells were regulated by BMSCs in a paracrine manner via the upregulation of osteogenic and migration-associated genes. A TGF-β receptor I inhibitor (LY3200882) significantly antagonized BMSC-induced biological activity and related gene expression in osteoblast-like cells. Interestingly, coculture with osteoblast-like cells significantly increased the production of TGF-β1 by BMSCs, and there was potential intercellular communication between BMSCs and osteoblast-like cells. Conclusions: Our findings provide evidence that the biological mechanism of BMSC-produced TGF-β1 promotes bone regeneration and repair, providing a theoretical basis and new directions for the application of BMSC transplantation in the treatment of osteonecrosis and bone injury.